Strategies for the Mediatization of Legal Concepts in Russian Mass Media of XXI Century (Concept LEGITIMACY) - O. N. Kondratyeva; Yu. S. Ignatova (Научный диалог, 2021)
The role of mass media in the processes of interpretation and assessment of various fragments of reality is discussed in the article. The problem of the entry of legal concepts into the media discourse is raised and the task is set to study the changes occurring in this process, which ultimately lead to the formation of new conceptual units — media concepts. The designated task is solved in the process of analyzing one of the key legal concepts LEGITIMACY. It has been demonstrated that the Russian mass media significantly modify each of the three components of the legal concept, that is, the media virus is “implanted” into the conceptual, figurative and value layers. It allows us to speak of three strategies of mediatization: definitional, metaphorical and evaluative. It is shown that the definitional strategy contributes to the emergence of new features in the conceptual layer of the LEGITIMACY concept (‘trust’, ‘approval’, ‘support’, ‘respect’, ‘fairness’, ‘the phenomenon of consciousness’ and ‘subjective feeling’). It is noted that the metaphorical strategy additionally forms such linguo-culturally specific features as ‘defectiveness’ and ‘object of political manipulation’, the evaluative strategy gives the positively perceived concept of LEGITIMACY a negative connotation (conceptual signs of ‘doubtfulness’ and ‘imaginary’ develop), which is an alarming marker reflecting the current situation in Russian society. It is pointed out that the recorded changes indicate the importance of the discursive factor in the study of concepts.